EVALUATION OF THE REVITALISATION OF MERDEKA SQUARE IN MEDAN CITY - Mayca Sita Nurdiana (Kalyanamitra: Journal of Archaeological Resource Management, 2025)
Merdeka Square of Medan City is a cultural heritage that has been designated based on the Decree of the Mayor of Medan. As a cultural heritage, besides being the city's identity and landmark, Merdeka Square also functions as a public space and green open space. The Medan City Government has carried out a revitalization project for Merdeka Square since 2022. The revitalization process should pay attention to conservation principles. The writing of this article aims to evaluate whether the revitalization process of Merdeka Square carried out by the Medan City Government is in accordance with the rules and guidelines of cultural heritage revitalization. So far, in principle, the revitalization process has paid attention to the objectives of cultural heritage conservation, but there are things that need to be criticized regarding its implementation, including destructive construction techniques and the lack of socialization to the community regarding the revitalization design and impact mitigation studies from the implementation of revitalization.